2005
DOI: 10.1111/j.1744-7410.2005.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and ultrastructural analysis of the epidermal gland cells of Branchiomma luctuosum (Polychaeta, Sabellidae)

Abstract: Abstract. This histochemical and ultrastructural study describes the epidermal gland cells of a tubicolous polychaete, Branchiomma luctuosum. The histochemistry was carried out using standard techniques and FITC‐labelled lectins. Four types of secretory cells were identified in two categories: orthochromatic cells (Type 1) and metachromatic cells (Types 2, 3, and 4). The secretory product of the Type‐1 orthochromatic cells contains neutral glycoproteins with Galβ1,3GalNAc residues. Metachromatic cells produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…In the Annellida Polychaeta the epidermal gland cells produce a mucus that has various functions thus mucus production constitutes a key factor determining the ability of many polychaete species to survive in their environment (Bonar, 1972). In sabellid polychaetes a heterogeneous mucus is involved in different functions, such as the prevention of the proliferation of pathogenic microorganisms, protection and absorption of metabolites, as well as the building of the tube (Mastrodonato et al, 2005). Mouneyrac et al (2003), in their studies on Hediste diversicolor, suggested that the secretion of mucus by gland cells in the epidermis is a specific response to toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…In the Annellida Polychaeta the epidermal gland cells produce a mucus that has various functions thus mucus production constitutes a key factor determining the ability of many polychaete species to survive in their environment (Bonar, 1972). In sabellid polychaetes a heterogeneous mucus is involved in different functions, such as the prevention of the proliferation of pathogenic microorganisms, protection and absorption of metabolites, as well as the building of the tube (Mastrodonato et al, 2005). Mouneyrac et al (2003), in their studies on Hediste diversicolor, suggested that the secretion of mucus by gland cells in the epidermis is a specific response to toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their mode of life, at least four alien species of Branchiomma have potential as invaders: B. luctuosum, originally described in the Red Sea, was first recorded by Giangrande (1989) as a non-indigenous species in the Mediterranean Sea. Since then, important records of B. luctuosum are present in Italian waters (Knight-Jones et al, 1991;Sordino & Gambi, 1992;Castelli et al, 1995;Gambi et al, 1998;Licciano et al, 2002;Mastrodonato et al, 2005), in the Aegean Sea (Arvanitidis, 2000;Simboura & Nicolaidou, 2001), on the Cypriot coasts (Ç inar, 2005), on the Levantine coast of Turkey (Ç inar et al, 2006), in the Gulf of Valencia and Balearic Islands, Spain (El Haddad et al, 2007) and in Brazil, south-western Atlantic ocean (Nogueira et al, 2006;Costa-Paiva et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…The first two segments of O. borealis adults possess glands associated with parapodia, and these are called PGOs. In annelids, glands that secrete the material used for forming a tube can be associated with the protruding parts of the animals, and these are usually parapodia (if present) in nereidids (Daly, 1973; Dorsett & Hyde, 1970), onuphids (Budaeva & Fauchald, 2011), Phyllodoce mucosa (Prezant, 1980), and spionids (Guggolz et al, 2015; Hedley, 1956a, 1956b; Müller & Hylleberg, & Michalik, 2015), or are anterior collar structures or ventral shield in sabellids and serpulids (Kryvi, 1972; Mastrodonato et al, 2005; Meyer, 1893; Vovelle, Rusaouen‐Innocent, Grasset, & Truchet 1994). The so‐called tube‐secreting glands are located on the ventral side, as in onuphids, sabellids, Spio species, oweniids, and alvinellids; the ventrolateral side, as in nereidids and serpulids; the dorsal side, as in clitellates; or around the entire worm, as in siboglinids (Budaeva & Fauchald, 2010; Daly, 1973; Dorsett & Hyde, 1970; Hedley, 1956a, 1956b; Kryvi, 1972; Malakhov & Galkin, 1998; Karaseva, Malakhov, & Galkin 2012; Vovelle et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The tube‐secreting glands are often restricted to the anterior part of the animal, which is the part that can extend from the tube, as is the case for oweniids (Guggolz et al, 2015; Smart & Von Dassow, 2009; Watson, 1901), nereids (Daly, 1973; Dorsett & Hyde, 1970), sabellids (Kryvi, 1972; Mastrodonato et al, 2005; Vovelle et al, 1994), the serpulid Pomatoceros triqueter (Hedley, 1956a, 1956b), spionids (Guggolz et al, 2015; Müller et al, 2015), and the alvinellid Alvinella pompejna (Vovelle & Gaill, 1986). Also in clitellates, the clitellum is in the anterior end of clitelliates and contains glandular cells that secrete the cocoon‐like slimy tube, which is used for the copulation (Morris, 1985; Suzutani, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation